Retention of lumpy skin disease virus in Stomoxys spp (Stomoxys calcitrans, Stomoxys sitiens, Stomoxys indica) following intrathoracic inoculation, Diptera: Muscidae - Issimov, A.; Taylor, D. B.; Shalmenov, M.; Nurgaliyev, B.; Zhubantayev, I.; Abekeshev, N.; Kushaliyev, K.; Kereyev, A.; Kutumbetov, L.; Zhanabayev, A.; Zhakiyanova, Y.; White, P. J. (My University, 2021)
Lumpy skin disease (LSD) is an emerging disease of cattle in Kazakhstan and the means of transmission remains uncertain. In the current study, retention of Lumpy Skin Disease Virus (LSDV) by three Stomoxys species following intrathoracic inoculation was demonstrated under laboratory conditions. A virulent LSDV strain was injected into the thorax of flies to bypass the midgut barrier. The fate of the pathogen in the hemolymph of the flies was examined using PCR and virus isolation tests. LSDV was isolated from all three Stomoxys species up to 24h post inoculation while virus DNA was detectable up to 7d post inoculation. © 2021 Issimov et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credit Неровная кожа (LSD) - это развивающееся заболевание крупного рогатого скота в Казахстане, и пути его передачи остаются неясными. В текущем исследовании в лабораторных условиях было продемонстрировано удержание вируса неровной кожи (LSDV) тремя видами Stomoxys после внутригрудной инокуляции. Вирулентный штамм LSDV вводили в грудную клетку мух, чтобы обойти барьер средней кишки. Судьбу патогена в гемолимфе мух исследовали с помощью ПЦР и тестов на выделение вируса. LSDV был изолирован от всех трех видов Stomoxys до 24 часов после инокуляции, в то время как ДНК вируса обнаруживалась до 7 дней после инокуляции. © 2021 г. Иссимов и др. Это статья в открытом доступе, распространяемая в соответствии с условиями лицензии Creative Commons Attribution License, которая разрешает неограниченное использование, распространение и воспроизведение на любом носителе при условии указания автора и источника.
PLoS ONE. - 2021
Keywords: импакт-фактор 2021; скопус; кларивате аналитикс; томсон; зарубежные авторы; зарубежное издание; дальнее зарубежье; научный журнал; периодическое издание; неровная кожа; кожное заболевание крс; вирус неровной кожи